2015
DOI: 10.1016/j.tiv.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Lead decreases cell survival, proliferation, and neuronal differentiation of primary cultured adult neural precursor cells through activation of the JNK and p38 MAP kinases

Abstract: Adult hippocampal neurogenesis is the process whereby adult neural precursor cells (aNPCs) in the subgranular zone (SGZ) of the dentate gyrus (DG) generate adult-born, functional neurons in the hippocampus. This process is modulated by various extracellular and intracellular stimuli, and the adult-born neurons have been implicated in hippocampus-dependent learning and memory. However, studies on how neurotoxic agents affect this process and the underlying mechanisms are limited. The goal of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Moreover, the involvement of ERK in adult NSPC regulation was further confirmed by the observation that both differentiation and survival were inhibited after the deletion of the ERK5 kinase [132]. There is also evidence indicating that other members of the MAPK family such as c-Jun N-terminal kinase (JNK) and p38 take part in the proliferation, differentiation and survival of adult NSPCs [133], which, although not induced by addictive drugs, nonetheless suggests the existence of similar pathways in drug addiction.…”
Section: Common Mechanisms In Adult Nspc Regulationmentioning
confidence: 98%
“…Moreover, the involvement of ERK in adult NSPC regulation was further confirmed by the observation that both differentiation and survival were inhibited after the deletion of the ERK5 kinase [132]. There is also evidence indicating that other members of the MAPK family such as c-Jun N-terminal kinase (JNK) and p38 take part in the proliferation, differentiation and survival of adult NSPCs [133], which, although not induced by addictive drugs, nonetheless suggests the existence of similar pathways in drug addiction.…”
Section: Common Mechanisms In Adult Nspc Regulationmentioning
confidence: 98%
“…Once absorbed in the body lead, cadmium, and PCBs can influence brain functioning by affecting neural cells, inducing oxidative stress, and lowering dopamine concentrations [46]. Age-related decreases in cognitive functioning is typical as life progresses, mild cognitive impairment (MCI) is a greater than average age-related change in cognitive functioning [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 27) showed that exposure of the rat cortex to lead induced apoptosis through the MAPK signaling pathway by phosphorylation of ERK and JNK. In addition, Engstrom et al 28) reported that lead-induced neurotoxicity in neural precursor cells is mediated by the activation of JNK and p38 and inhibition of prosurvival Akt signaling. 28) In the present study, activation of ERK (Figs.…”
Section: +mentioning
confidence: 99%
“…In addition, Engstrom et al 28) reported that lead-induced neurotoxicity in neural precursor cells is mediated by the activation of JNK and p38 and inhibition of prosurvival Akt signaling. 28) In the present study, activation of ERK (Figs. 3A, 4) and p38 (Fig.…”
Section: +mentioning
confidence: 99%